Answer:
f(9) = f(8)·(-3)
Step-by-step explanation:
A recursive function is one where each successive term is calculated using the previous term;
The clear pattern demonstrated in the sequence of terms shown is that each term is multiplied by -3 to give the next one;
Hence, the correct option is the first.
Answer:
26.25-7.50 = 18.75
18.75/6.25= 3
She golfed for 3 rounds
Step-by-step explanation:
Answer:
A. 0
Step-by-step explanation:
<span>-6f+13=2f-11
-6f - 2f = -11 - 13
-8f = -24
f = 3</span>
Answer: 15.55 miles
Step-by-step explanation:
in 3 days, Samuel ran 8+4.25+3.3=15.55 miles